2015
DOI: 10.1002/cbic.201500496
|View full text |Cite
|
Sign up to set email alerts
|

Identifying the Minimal Enzymes Required for Biosynthesis of Epoxyketone Proteasome Inhibitors

Abstract: Epoxyketone proteasome inhibitors have attracted much interest due to their potential as anti-cancer drugs. While the biosynthetic gene clusters for several peptidyl epoxyketone natural products have recently been identified, the enzymatic logic involved in the formation of the terminal epoxyketone pharmacophore has been relatively unexplored. Here, we report the identification of the minimal set of enzymes from the eponemycin gene cluster necessary for the biosynthesis of novel metabolites containing a termin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 14 publications
(23 citation statements)
references
References 27 publications
0
23
0
Order By: Relevance
“…During the preparation of our manuscript, Liu et al. published a study on the identification of the minimal gene cluster for the biosynthesis of epoxyketone proteasome inhibitors and came to the same conclusions . They showed that in an E. coli heterologous system, only the genes for the NRPS/PKS machinery ( epnG / epnH ), the acyl CoA‐dehydrogenase ( epnF ), and the external addition of fatty acids are necessary to produce an epoxyketone compound.…”
Section: Figurementioning
confidence: 47%
See 4 more Smart Citations
“…During the preparation of our manuscript, Liu et al. published a study on the identification of the minimal gene cluster for the biosynthesis of epoxyketone proteasome inhibitors and came to the same conclusions . They showed that in an E. coli heterologous system, only the genes for the NRPS/PKS machinery ( epnG / epnH ), the acyl CoA‐dehydrogenase ( epnF ), and the external addition of fatty acids are necessary to produce an epoxyketone compound.…”
Section: Figurementioning
confidence: 47%
“…During the preparation of our manuscript,L iu et al published as tudy on the identification of the minimal gene cluster for the biosynthesis of epoxyketonep roteasome inhibitors and came to the same conclusions. [8] They showedt hat in an E. coli heterologouss ystem,o nly the genes for the NRPS/PKS machinery (epnG/epnH), the acyl CoA-dehydrogenase (epnF), and the externala ddition of fatty acids are necessary to produce an epoxyketone compound. Feeding of isotope-enriched precursors in the same setupa nd MS analysis indicated that two methylg roups are incorporateda nd one carbon from acetate is lost by decarboxylation duringe poxyketoneb iosynthesis.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations